PENGARUH PEMBERIAN EKSTRAK GEMBILI (Dioscorea esculenta) TERHADAP PERTUMBUHAN VOLUME ADENOCARCINOMA MAMMAE MENCIT BETINA C3H Studi Eksperimental pada Mencit Betina Strain C3H yang Telah Diinokulasi dengan Bubur Tumor - Agus Suprijono; - Sumarno; Lisa Rachmayanti (Majalah Ilmiah Sultan Agung, 2012)
The incidence of breast cancer (Adenocarcinoma mammae) has been increasing. Gembili extract (Dioscorea esculenta) has been know to have an active substanced called dioscin and diosgenin having anti-oksidan and anti inflammatory property. Few studies have been done to determine the effect of gembili extract (Dioscorea esculenta) on the growth of adenocarcinoma mammae. The purpose of this study was to find out the effect of gembili extract (Dioscorea esculenta) on the volume of adenocarcinoma mammae in C3H female mice.In this experimental study using Pre-post test control group design, 24 C3H female mice were randomly devided into 4 groups of 6 mice each treated for 21 days. Group I (control) was inoculated with cancerous tissue and fed a standard diet and drinking water. Group II, III, IV were inoculated with cancerous tissue, fed a standard diet and drinking water and treated with gembili extract (Dioscorea esculenta) at the dose of 100 mg/kgBW/d, 150 mg/kgBW/d, 200 mg/kgBW/d respectively. The volume of adenocarcinoma mammae was recorded before and after the treatment with Kaliper instrument. Saphiro wilk followed by Pair T-test was applied for the data analysis. The study showed a significant difference in the volume of adenocarcinoma mammae in group IV. No statistically significant difference found in group II and III. It can be concluded that gembili extract (Dioscorea esculenta) effects on the growth of adenocarcinoma mammae in C3H female mice.Â Â Keywords: Gembili Extract (Dioscorea esculenta), Adenocarcinoma mammae, Volume Growth.